The Musicologies in Brazilian Reality: the Game of Knowledge and its Paradoxes - Sant Ana, Edson Hansen [UNESP] (Univ Estadual Parana, Escola Musica & Belas Artes Parana, 2016)
This text aims to address some issues and problems that concern the performance of the (s) Musicology (s) in the current Brazilian situation. Some questions are raised in the light of Denis Laborde, French musicologist; Paulo Costa Lima, Brazilian composer and musicologist critical; and Jos D'Assuncao Barros (2013), musician, writer, theoretical and Brazilian historian. Additionally develop questions and statements in the sense of audience research in more empirical and more speculative Music proposing a libertarian view with respect to the form and watertight theories stemmed from the dominant academic centers, however highlighting the importance of theoretical and methodological logic, I dare present a posture innovative and inventive when it comes to new searches, interpretations and seemingly disparate theories associations, the suggestion of making studies in music more coherent posture of a science of music that behaves as ' science'.
Keywords: Composition; Musicology Undisciplined; New Paradigms; Speculative Search; Knowledge and Power